Identification of new resistant varieties to Phomopsis fruit rot of eggplant (Solanum melongena) - BHANUSHREE N; B S TOMAR; JAMEEL AKHTAR; PARTHA SAHA (The Indian Journal of Agricultural Sciences, 2022)
Eggplant (Solanum melongena L.) is one of the supreme members of the solanaceous group which is widely grown in India. It is considered as the single and economic host of the fungus Diaporthe vexans causing fruit rot, stem canker and blight disease. The present study was carried at the vegetable research farm of ICAR-Indian Agricultural Research Institute, New Delhi during 2019–20 and 2020–21 to screen the eggplant lines (18 cv.) for resistance against this pathogen. The pathogen was isolated from the infected fruits and confirmed by morphological and sequencing information. Artificial inoculation using pin prick method revealed the presence of variability in the lines for disease. The studied lines were categorized based on Per cent disease index (PDI) and the highest PDI value of 80–100% recorded in cultivars Pusa Shyamla, Pusa Kranti, DBL-186, DBL-187, Muktokeshi and DBSR-52 and thus categorized as highly susceptible. The cultivars NDB-25, Kashi Sandesh, Kalo Solia, DBL-175 and Debjhuri Hazari were reported to be susceptible with PDI value of 60%. In the present study, first time we have report a number of highly resistant lines, viz. BR 112, Swarna Mani, BR 40-7 and IC-112992 with 0% PDI as novel source of resistance against P. vexans. These resistant lines have significant importance in large scale cultivation as resistant varieties by farmers. They can also be further utilized as a parent in population development for the identification of gene (s)/ QTL (s) associated with the resistance.